Immunological markers as predictors of developing steroid-induced diabetes mellitus in pemphigus vulgaris patients: An observational study. Issue 17 (April 2018) - Dănescu, Ana Sorina; Bâldea, Ioana; Leucuţa, Daniel Corneliu; Lupan, Iulia; Samaşca, Gabriel; Sitaru, Cassian; Chiorean, Roxana; Baican, Adrian
Abstract : Abstract: The aim of this study was to evaluate the clinical importance of autoantibodies in pemphigus vulgaris patients who developed steroid-induced diabetes mellitus (SID) because of the glucocorticoid therapy of pemphigus. A total of 137 patients with pemphigus vulgaris were studied. Patients with SID and pemphigus were compared with those that had only pemphigus. The variables recorded were: age at diagnosis, sex, body mass index, presence of diabetes mellitus (DM), cumulative cortisone dose, treatment duration, value of anti-desmoglein 1 and 3, and anti-glutamic acid decarboxylase autoantibodies. A total of 31 patients (22.62%) that developed steroid-induced DM were identified. Anti-glutamic acid decarboxylase autoantibodies were positive in 20.75% of patients with pemphigus vulgaris and in 25.75% of patients with pemphigus vulgaris and SID. The overall anti-glutamic acid decarboxylase autoantibodies prevalence in pemphigus patients was high, and the risk of developing DM in patients with pemphigus remains a serious problem, being associated with increased risk of mortality.